Polioencephalomalacia in Sheep - Clinical and Magnetic Resonance Imaging Findings - Cerri, Fabrício Moreira; Cardoso, Isabella Mendonça Zanella Cecconi; Machado, Vânia Maria de Vasconcelos; Oliveira-Filho, José Paes de; Amorim, Rogério Martins; Borges, Alexandre Secorun; Andrade, Danilo Giorgi Abranches de (Acta Scientiae Veterinariae, 2022)
Background: Polioencephalomalacia (PEM) is a neurological disease in ruminants, which is characterized by malacia of brain gray matter. Thiamine deficiency and sulfur intoxication are the most common causes of PEM in sheep. Affected animals present signs of cerebrocortical syndrome, including amaurosis, ataxia, head pressing, mental depression, seizures, and opisthotonus. The neurological examination aims to determine the neurolocalization of the lesions and advanced imaging techniques are useful for confirming the affected area(s) in the central nervous system. The aim of this study is to describe clinical features and ante-mortem diagnosis using magnetic resonance imaging (MRI) in a sheep with PEM. Case: An 18-month-old male Dorper sheep from a flock started receiving concentrate 7 days before. According to the owner, no clinical signs of abnormality were observed on the previous morning. However, in the afternoon, the animal became self-isolated and did not follow the flock to the sheepfold. The following day, he was found in recumbency. Physical examination revealed lateral recumbency, rectal temperature 39.5ºC, 52 bpm, 120 bpm, congested mucous membranes, capillary refill time 1 s, ruminal (4/5 min) and intestinal hypomotility. The assessment of the central nervous system revealed a decreased level of consciousness, focal seizures, opisthotonus, and absence of menace response. The following differential diagnoses were listed: PEM, head trauma, focal symmetrical encephalomalacia, bacterial encephalitis, and rabies. Treatment was composed of dexamethasone [0.2 mg/kg - i.v., SID (1st-3rd day), 0.1 mg/kg, i.v., SID (4th-6th day), and 0.05 mg/kg, i.v., SID (7th-9th day)]; mannitol [1 g/kg - i.v. and diazepam 0.4 mg/kg, i.v. single dose at admission]; vitamin B1 [10 mg/kg - i.m., SID], furosemide [1 mg/kg - i.v., SID for 3 days] and sulfadoxine/trimethoprim [30 mg/kg - i.m., SID for 10 days]. After the initial treatment, the patient showed mild clinical improvement; however, the amaurosis was still present. Magnetic resonance imaging of the brain was performed on the 2nd day of hospitalization, showing a symmetrical hypersignal in the parietal and occipital cortices, in the axial and sagittal sequences weighted in T2 and FLAIR. Discussion: This study aimed to describe the clinical signs and MRI findings in a sheep with PEM. In this case, the sudden change to the feed composition probably led to ruminal dysbiosis, inhibition of thiamine-producing microorganisms and proliferation of bacteria that synthesize thiaminase. Thiamine therapy proved to be effective and capable of reverting the clinical signs. The decrease in the level of consciousness, cortical blindness, and opisthotonus are due to alterations in the parietal cortex, in the occipital cortex, and in the cerebellum, respectively, which were demonstrated by hypersignal areas in the MRI. Therefore, the neurolocalization of the lesion based on neurologic examination and the MRI findings were related. The physicochemical and cytological evaluations of the cerebrospinal fluid, and dosage of thiamine and the concentration of hydrogen sulphide in the rumen were not performed. However, the response to thiamine treatment associated with the neurologic examination and MRI findings helped in determining the diagnosis. Additionally, MRI can be used as a useful tool for the ante mortem diagnosis of PEM. Keywords: cerebrocortical necrosis, diagnostic imaging, neurology, ruminants, thiamine deficiency.